Understanding the authenticity of traditional housing in Algeria: keys to intervening in heritage spaces of mozabit housing - Moufida, Sebti; Faten, Ghanemi; Djamel, Alkama (Indonesian Journal of Social Science Research, 2024)
The human settlement of M'zab is a traditional habitat located in the Sa-hara of Algeria; it considered by its richness in bioclimatic elements and distinguished by a typological variety. This study aims to discover the traditional habitat in the Sahara of Algeria, by shedding light on the con-structive richness in the habitat of M'zab according to its natural context. We used an analytical approach to examine the fundamental aspects: the natural context, the morphology, housing and the construction. To carry out this study, we carried out numerous field visits, including taking pho-tographs, direct surveys and in-depth discussions with specialists. These initiatives have enriched our understanding of the specificities of the habitat studied. The habitat of M'zab opened the doors to the discovery of traditional habitat in Algeria, which harmonizes perfectly with its cli-matic and natural environment. In addition, it allowed us to understand in more depth the intervention strategies in the heritage areas of the Sa-hara, while drawing valuable lessons from the past.